The tradition of Bele Kampung Malay In Pelanduk Mandah Indragiri (semiotic analysis) - Raja Wiwin; Elmustian; Silvia Permatasari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to analyze the meaning of denotative semiotics and the meaning of connotative in the malay village bele tradition found in the village of Pelanduk Mandah Indragiri. The meaning of denotative semiotics and connotative semiotic meaning were obtained, namely in the form of objects and equipment used during traditional processions or ritual carried out in the village of Pelanduk Mandah Indragiri. This study used deskriptive qualitative method. Qualitative descriptive research is a method used to describen analyze, and summrize various situations and conditions from varius data in the form of observatuons about problems. Data collection techniques in this study are observation techniques, interview techniques. The results of this study found 27 datums in the from of objects and equipment used and have denotative meanings and connotative meanings.